The case for reintroduction: The jaguar (Panthera onca) in the United States as a model. Issue 6 (1st May 2021) - Sanderson, Eric W.; Beckmann, Jon P.; Beier, Paul; Bird, Bryan; Bravo, Juan Carlos; Fisher, Kim; Grigione, Melissa M.; López González, Carlos A.; Miller, Jennifer R. B.; Mormorunni, Cristina; Paulson, Laura; Peters, Rob; et al.
Abstract: Reintroduction—defined here as the return of a species to a part of its range where it has been extirpated—is a critical pathway to conservation in the 21st century. As late as the 1960s, jaguars ( Panthera onca ) inhabited an expansive region in the central mountain ranges of Arizona and New Mexico in the United States, a habitat unique in all of jaguar range. Here, we make the case for reintroduction, building a rhetorical bridge between conservation science and practice. First, we present a rationale rooted in the philosophy of wildlife conservation. Second, we show that the species once occupied this territory and was extirpated by human actions that should no longer pose a threat. Third, we demonstrate that the proposed recovery area provides suitable ecological conditions. Fourth, we discuss how return of the species could be a net benefit to people, explicitly recognizing a diversity of values and concerns. Fifth, we show that reintroduction is practical and feasible over a realistic time horizon. Returning the jaguar to this area will enhance the recovery of an endangered species in the United States, further its range‐wide conservation, and restore an essential part of North America's cultural and natural heritage.